2009
DOI: 10.1007/s11596-009-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

RASSF2A promoter methylation in hepatitis B virus-related hepatocellular carcinogenesis and its correlation with elevated serum α-fetoprotein level

Abstract: Loss of the RASSF2A expression induced by methylation-mediated silencing has been reported in several human cancers, but the methylation status of RASSF2A in hepatocellular carcinoma (HCC) is rarely studied so far. In this study, we investigated the RASSF2A expression and its methylation status in a cohort of 45 hepatitis B virus-associated HCC tissues and their adjacent non-carcinoma tissues by using RT-PCR and MS-PCR. Promoter methylation of RASSF2A was found in 31 (68.9%) out of 45 HCC tissues and 12 (40%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…They also observed that gastric cancers with methylation at U1 and D1 exhibited significantly less frequent lymphatic permeation than unmethylated gastric cancers. Afterwards, epigenetic inactivation of RASSF2 was found in oral squamous cell carcinoma (16), head and neck squamous cell carcinoma (26), hepatocellular (27) and thyroid cancers (28). Although a previous study demonstrated that expression of the RASSF2 gene is silenced by methylation in human gastric cancer (29), the authors did not clarify the clinical impact of RASSF2 expression or the prognostic value for patients with gastric cancer since the number of cases was too small.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that gastric cancers with methylation at U1 and D1 exhibited significantly less frequent lymphatic permeation than unmethylated gastric cancers. Afterwards, epigenetic inactivation of RASSF2 was found in oral squamous cell carcinoma (16), head and neck squamous cell carcinoma (26), hepatocellular (27) and thyroid cancers (28). Although a previous study demonstrated that expression of the RASSF2 gene is silenced by methylation in human gastric cancer (29), the authors did not clarify the clinical impact of RASSF2 expression or the prognostic value for patients with gastric cancer since the number of cases was too small.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of global levels of DNA methylation of human HCC samples, the RASSF2 gene is preferentially inactivated by promoter hypermethylation in a subgroup of patients with better survival . However, the prognosis impact of RASSF2 inactivation still remains unclear as patients with HBV‐associated HCC with a methylated RASSF2A promoter have relatively higher serum AFP levels and a poorer prognosis than unmethylated tumour .…”
Section: The Ras/mapk Pathway In Hepatocarcinomamentioning
confidence: 99%
“…All of these isoforms contain Ras association (RA) domains, but only RASSF2A has an associated CpG island (Hesson et al, 2005). Down-regulation of RASSF2A by promoter hypermethylation has been shown in different tumor cell lines and primary tumors, which suggests that RASSF2A participates in carcinogenesis (Vos et al, 2003;Akino et al, 2005;Endoh et al, 2005;Park et al, 2007;Zhang et al, 2007;Ren et al, 2009).…”
Section: Aberrant Methylation Of Rassf2a In Tumors and Plasma Of Patimentioning
confidence: 99%